THE NEEDS FOR DEVELOPING COOPERATIVE PROBLEM-BASED LEARNING (CO-PBL) TO PROMOTE VERBAL CREATIVITY IN EFL WRITING - Ghufron, M. Ali; Ermawati, Siti (LPPM Undiksha, 2018)
This study is the initial part for developing cooperative problem-based learning (hereafter Co-PBL) to promote verbal creativity in EFL writing. The study is aimed at: (1) investigating the previous teaching and learning model implemented in EFL writing class; and (2) measuring and analyzing the extent to which the teachers and students need Co-PBL to promote verbal creativity (hereafter VC) in EFL writing. This study employed a case study method with the respondents of the research were 2 EFL writing teachers and the students who take EFL writing course in English Education Department of a private university in East Java, Indonesia. The data was yielded from questionnaire, in-depth interview, observation, and document analysis. After analyzing the data descriptively, the results show that teachers have used to implement cooperative learning and problem-based learning in EFL writing class; however, they never try to integrate the two models as a new one. It was also revealed that they did not notice verbal creativity as an affecting factor in EFL writing due to their insufficient knowledge to develop learning model that can promote verbal creativity. This study also reveals that teachers and students are eager to develop and implement Co-PBL in order to promote studentsâ verbal creativity in EFL writing. The findings of this study might have implication for EFL writing teachers and learners.